Algunas observaciones sobre la biología de la Dermatobia hominis (L. Jr.) y el problema del tórsalo en Costa Rica - Zeledón, Rodrigo (1957)
Some biological aspects are studied of the human bot fly Dermatobia hominis, which attains rather large proportions in Costa Rica. In some areas where the bot is abundant, the stable-fly Stomoxys calcitrans acts in a rather Stomoxys is present with fair Dermatobia eggs, it is easy to understand high percentage as a carrier for the eggs. Since regularity in human dwellings carrying that measures taken to control the former may serve to decrease the incidence of the latter on animals and humans. Several experiments are described on pupation of the mature larva in which various material s were used-damp soil, dry soil, wood shavings, excelsior, and blotting paper in the bottom of the flasks. Although the experiments were made in small scale, they have some significance in that they tend to show no appreciable differences in the larvae's ability to pupate and their viability in the various media. The substrate seems to act simply as an absorbent of the excess of liquid which the larva must eliminate as the construction of its pupary is begun. If the process is not carried out under such conditions, pupation in general is imperfect, as was shown when mature larvae were placed in a flask without any absorbent material of any kind. The fact that the larvae show an instinct to bury themselves may be explained as a defense against excessive heat in the superficial soil layers, as experiments in a culture oven showed that a temperature of 32° C. is enough to sterilize them. It was also possible to shorten the pupal period to a minimum duration of 20 days at a constant temperature of 30° C. Adults were observed to live at room temperature from 4 to 12 days; an in crease in temperature decreased their life span, as all adults hatched at 30° C. lived 2 days at the most. Copulation may begin the first day after hatching, and egg-laying three days after. Larvae were recorded hatching from eggs laid on laboratory and on 2 Musca domestica Stomoxys calcitrans captured with apparently 9, 9, and 8 days respectively. in the fresh-laid eggs. The periods of incubation were Various animals were infected with these larvae, and in a dog infected with a larva from the second Stomoxys, the complete cycle was observed, as follows : development of the egg, 8 days ; development of the larva, 33 days (it was removed) ; pre-pupal period, 2 days; pupal period, 37 days; adult period, 5 days; total 85 days. The decisive influence of temperature on each of these periods is emphasized. Some remarks are made on the possibility of using atomic radiation to combat and control bot flies.